Danggui Niantong granules ameliorate rheumatoid arthritis by regulating intestinal flora and promoting mitochondrial apoptosis - Qi-Jin Lu; Jia-Yu Li; Hong-Xin Lin; Yi-Si Cai; Chang-Shun Liu; Li-Ping Fu; Gang Liu; Li-Xia Yuan (Taylor & Francis Group, 2022)
Context Danggui Niantong Granules (DGNTG) are a valid and reliable traditional herbal formula, commonly used in clinical practice to treat rheumatoid arthritis (RA). However, the mechanism of its effect on RA remains unclear.Objective An investigation of the therapeutic effects of DGNTG on RA.Materials and methods Twenty-four male Sprague-Dawley (SD) rats were divided into four groups: control, model, DGNTG (2.16 g/kg, gavage), methotrexate (MTX) (1.35 mg/kg, gavage) for 28 days. The morphology of synovial and ankle tissues was observed by haematoxylin-eosin staining. The responses of mitochondrial apoptosis were assessed by qPCR, Western blotting and immunohistochemical staining. Rat faeces were analysed by 16S rRNA sequencing.Results Our results showed that DGNTG treatment reduced AI scores (7.83 ± 0.37 vs. 4.67 ± 0.47, p < 0.01) and paw volumes (7.63 ± 0.17 vs. 6.13 ± 0.11, p < 0.01) compared with the model group. DGNTG also increased the expression of Bax (0.34 ± 0.03 vs. 0.73 ± 0.03, p < 0.01), cytochrome c (CYTC) (0.24 ± 0.02 vs. 0.64 ± 0.01, p < 0.01) and cleaved caspase-9 (0.24 ± 0.04 vs. 0.83 ± 0.08, p < 0.01), and decreased bcl-2 (1.70 ± 0.11 vs. 0.60 ± 0.09, p < 0.01) expression. DGNTG treatment regulated the structure of gut microbiota.Discussion and conclusions DGNTG ameliorated RA by promoting mitochondrial apoptosis, which may be associated with regulating gut microbiota structure. DGNTG can be used as a supplement and alternative drug for the treatment of RA; its ability to prevent RA deserves further study.